Blockchain study - Chao, Shan Te (Nanyang Technological University, 2020)
Blockchain is a very exciting and promising technology that emerged in this time and age. Ever since 2008 when Satoshi Nakamoto invented the Blockchain Technology (BT), we have seen blockchain evolving from Blockchain 1.0 (The Bitcoin) to Blockchain 2.0 (Smart Contract) and today, Blockchain 3.0 that aims to improve the issues and flaws from the previous generations. Ten years down the road, the awareness of blockchain has evolved to not just being known as cryptocurrency and the trading of the coins, but the unique characteristics of the technology itself are becoming more recognised and appealing to business services than ever before. The BT today, has advanced to Blockchain 3.0, where improvements are made to flaws identified from previous generations and more developers are exploring ways to adopt the technology in the Internet of Things (IoT). However, there are still many challenges faced that are hindering the growth and adoption of BT by businesses and they remain persistent even in today’s context. In this study report, we will have two separate components: 1) Understanding one of the challenges of BT today – scalability, and study on off-chain approaches. 2) Hands-on understanding of basic blockchain via the implementation of a blockchain network and proof of concept application for NTU campus. The objective of this study report is to look into the challenges of BT and discuss further on the scalability issue and off-chain approaches. The study of scalability and off-chain approaches shall provide some insights to benefits, design patterns, solutions and considerations that stakeholders and developers can reference in their blockchain project that look to scale and stay future proof. As well as documentation of implementing a dedicated blockchain network for the campus as a separate part of the study.